MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PROSES CUTTING DI DIVISI KAPAL PERANG PT. PAL INDONESIA (PERSERO) - Kartika Sari, Rizqy; Harjono, Afrian Eskartya (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
Introduction: The implementation of occupational safety and health is one form of effort to create a safe, healthy and prosperous work environment, free from work accidents and occupational diseases, and free of environmental pollution towards increased productivity including the implementation of Occupational Safety and Health Management. Methods: This study aims to see an overview of occupational safety management. The research was conducted in the cutting process at the Warship Division of PT PAL Indonesia (Persero) in 2022. This research is an observational study. Data collection was carried out through observation, discussion, interviews and literature studies related to process flow and work environment measurements. Data analysis using the HIRADC method. Results: Based on the risk management of the cutting process in the Warship Division of PT PAL INDONESIA (Persero), there are 7 hazards that pose a risk. Risks have varying severity and frequency. The most frequent and severe type of risk is fire. Conclusion: The risk control that has been implemented is good, as evidenced by the decrease in the risk category in the residual risk, which is a low and medium risk category. PT PAL INDONESIA Warship Division is very committed in implementing risk control.